Faktor Pendorong Partisipasi Pengguna Internet dalam Petisi Digital - Dyah Hapsari Ekonugraheni; Retna Mahriani; Yusnaini Yusnaini (Society, 2023)
This study tries to answer why citizens of the Republic of Indonesia continue to participate in digital petitions even though the government has not legalized this mechanism. To answer this question, the researchers used raw data from the World Value Survey (WVS) VII, which involved 3,000 respondents from Indonesia who were eighteen years old and randomly selected. The logistic regression technique examined the effect of fourteen independent variables on the dependent variable (internet user participation in digital petitions/Y). The final logistic regression model contains seven independent variables that can explain Y as much as 4.52% significantly, X2 (7) = 169.60, p < 0.01. The final model produces the characteristics of respondents who could participate in digital petitions: young people, not religious, having liberalism ideology, male, educated more than or equivalent to high school, distrust of government organizations, and unmarried. This study recommends that the government and parties related to digital petitions increase citizens’ religiosity, increase the quantity, access, and quality of education levels of ideological education, and maintain citizens’ trust in government organizations. Researchers also encourage the legislative institutions at the central and local levels to formally adopt the digital petition mechanism as an official channel for citizens to articulate their political aspirations.